Long‐term austral summer wind speed trends over southern Africa. (5th October 2016) - Nchaba, Teboho; Mpholo, Moeketsi; Lennard, Chris
ABSTRACT: A comprehensive analysis of near surface (10‐m and 850 hPa) long‐term (1980–2015) austral summer mean wind speed trends over southern Africa and the surrounding oceans (10°–40°S and 10°W‐50°E) is carried out. The climate forecast system reanalysis and the climate forecast system reanalysis version 2, the modern era retrospective‐analysis for research and applications version 2, and the ERA‐Interim products are used for the analysis. Trends are estimated using the Theil–Sen slope estimator and their significance tested with the Mann–Kendall test. Attribution of the wind speed trends to large scale circulation systems is determined from: (1) trends in 850 hPa geopotential height, surface pressure, and surface skin temperatures, (2) changes in the annual frequency of archetypal synoptic states generated by self‐organizing maps from geopotential height data, and (3) the correlations of the wind speeds to the southern annular mode (SAM) and El Niño Southern Oscillations (ENSO) indices. There is an overall decline in wind speeds evident in all the reanalyses. Wind speeds reduce by an average 0.7 and 1.3 m s −1 at 10 m and 850 hPa, respectively, over the study period. Deceleration in midlatitude westerly and Atlantic south easterly winds are associated with a poleward shift in the subtropical anticyclone, a positive trend in the annual frequency of summer circulation weather types, and the weakening of the subtropical continental heat low. The SAM and ENSO are also found to have a statistically significant linear association with the observed wind speed trends.